Non-invasive assessment of liver fibrosis staging in chronic hepatitis B patients: combining two-dimensional shear wave elastography with serum indicators - Zhang, Yaoren; Yang, Jianjun; Wan, Qinyun; Gan, Lu; Liu, Jianxue (Frontiers in Medicine, 2026)
ObjectiveThis study aimed to evaluate the diagnostic accuracy of a novel approach that combines noninvasive indicators with two-dimensional shear wave elastography (2D SWE) to assess liver fibrosis stages in patients with chronic hepatitis B (CHB), using the Scheuer score as the reference standard.Methods and materials2D SWE and serum indicators are commonly used for the noninvasive assessment of liver fibrosis. A total of 102 patients with CHB underwent 2D SWE measurements and serum tests for liver fibrosis markers. Standardized protocols were followed for all diagnostic procedures to ensure reproducibility and consistency. Binary logistic regression was used to generate a combined predictive probability value. Receiver operating characteristic (ROC) curves were used to evaluate the efficacy of the noninvasive diagnosis of liver fibrosis stages.ResultsCombining multiple serum indicators increased the AUC for diagnosing substantial liver fibrosis from 0.735 (0.650–0.810) to 0.825 (0.746–0.888) (p = 0.016), for severe liver fibrosis from 0.815 (0.730–0.881) to 0.881 (0.810–0.932) (p = 0.024), and for cirrhosis from 0.904 (0.823–0.923) to 0.954 (0.900–0.984) (p = 0.013). The AUC for diagnosing substantial liver fibrosis increased from 0.805 (0.725–0.858) to 0.889 (0.820–0.939) (p = 0.040) with the combined serum indicators and 2D SWE, indicating a clinically meaningful improvement in diagnostic accuracy.ConclusionThe combination of multiple noninvasive indicators can improve the accuracy of assessing liver fibrosis stages in patients with CHB. This approach offers a potential noninvasive alternative to liver biopsy for assessing liver fibrosis, particularly in advanced stages that require clinical intervention.